Biocompatibility and Surface Characteristics of Resin-Modified Glass Ionomer Cements with Ammonium Quaternary Compounds or Silver Nanoparticles: An In Vitro Study. (2nd October 2018) - Munguía-Moreno, Silvia; Martínez-Castañón, Gabriel-Alejandro; Patiño-Marín, Nuria; Cabral-Romero, Claudio; Zavala-Alonso, Norma-Verónica
Abstract : Glass ionomer cements are materials with diverse clinical applications. Its use is indicated in patients with special needs, pediatric patients, and the elderly; accordingly, it is important to know its properties. The aim of the present study was to determine the cytotoxicity, surface roughness, microhardness, and surface characteristics of GC Fuji ORTHO LC and GC Fuji PLUS resin-modified glass ionomer cements (RMGICs) with 1 and 2% of benzalkonium chloride, cetylpyridinium chloride, hexadecyltrimethylammonium bromide, or silver nanoparticles. All the experimental groups increase or decrease statistically significantly the VHN (P < 0.05 ) compared with the control group, except for GC Fuji PLUS added with hexadecyltrimethylammonium bromide 1 wt%. In the same way, all groups show a statistically significant (P < 0.05 ) increase or decrease in Ra compared with the control group except for GC Fuji ORTHO added with benzalkonium chloride 2 wt%, GC Fuji PLUS added with benzalkonium chloride 2 wt%, and GC Fuji PLUS added with cetylpyridinium chloride 2 wt%. The SEM micrographs show similar surface images between the control and experimental groups. When a dental material is modified, it is important to reevaluate its biological and mechanical characteristics. In the present study, all the additions modified the cytotoxicity and surface characteristics of RMGICs, by increasing or decreasing these properties.